Practical research : - Leedy, Paul D. (Pearson Education, 2015)
This book is a do-it-yourself, understand-it-yourself manual for planning and conducting research. Suitable for a wide variety of courses in basic research methodology, the text guides the reader, step-by-step, from the selection of a problem, through the process of conducting authentic research, to the preparation of a completed report, with practical suggestions throughout